Structures Congress 2013 2013
DOI: 10.1061/9780784412848.106
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Affordable Seismic Retrofit of Substandard Confined Masonry

Abstract: Confined masonry (CM) consists of unreinforced masonry walls confined with reinforced concrete tie columns and beams. Due to satisfactory performance during past earthquakes, CM has become the predominant construction style in several developing countries. However, poor construction practices and substandard materials may result in inadequate performance.This paper evaluates the feasibility and efficiency of an affordable and practical retrofit technology designed for CM constructions in developing areas. Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Note that in determination of the compressive capacity of the FT (F YFT ), which is determined considering axial force-flexural moment interaction, the effects of the generated bending moments at the base of this tie is also considered. This assumption is valid considering moments in the form of horizontal cracks at the tensile face in ties have been reported [28,33,[42][43][44][45][46][47][48]. It can generally be concluded that the lower the L/H, the higher the forces and the higher the generated moments in the ties are.…”
Section: Numerical Simulation Approach and Calibrationmentioning
confidence: 99%
“…Note that in determination of the compressive capacity of the FT (F YFT ), which is determined considering axial force-flexural moment interaction, the effects of the generated bending moments at the base of this tie is also considered. This assumption is valid considering moments in the form of horizontal cracks at the tensile face in ties have been reported [28,33,[42][43][44][45][46][47][48]. It can generally be concluded that the lower the L/H, the higher the forces and the higher the generated moments in the ties are.…”
Section: Numerical Simulation Approach and Calibrationmentioning
confidence: 99%